PENGARUH KEPRIBADIAN DOSEN DAN MOTIVASI KERJA TERHADAP KINERJA DOSEN DENGAN DIMEDIASI OLEH KEPUASAN KERJA (Studi Kasus Pada Dosen Politeknik Ilmu Pelayaran Semarang) - Hary Sumpeno, 11.50.02.0023 (Students Journal of Economic and Management, 2013)
Target of this research to test influence personality of motivation and lecturer to lecturer performance with mediation by satisfaction work lecturer in is Polytechnic of Navigation Semarang. Pursuant to the mentioned hence this research take title âPengaruh Kepribadian Dosen Dan Motivasi Kerja Terhadap Kinerja Dosen Dengan Dimediasi Oleh Kepuasan Kerja (Studi Kasus Pada DosenÂ Politeknik Ilmu Pelayaran Semarang)â. In this research take Polytechnic Lecturer population of Navigation Semarang amounting to 93 people with sampling census method technique taking all existing population. Used by data is primary data and data analysis use doubled linear regression. Pursuant to result of research which have been done by hence can know by personality have an effect on to satisfaction of job, motivation have an effect on to satisfaction of job, personality have an effect on to lecturer performance, motivation have an effect on to lecturer performance and satisfaction of job have an effect on to lecturer performance. Satisfaction work personality mediation to lecturer performance because indirect influence bigger than at direct influence and satisfaction work mediation motivate to lecturer performance because indirect influence bigger than at direct influence. Keyword : personality, motivate, satisfaction work and lecturer performance